MOVING THROUGH A EUROPEAN DEFENCE LANDSCAPE OF BLURRED OUTLINES: SPANISH DEFENCE AND THE DEVELOPMENT OF A COMMON SECURITY AND DEFENCE POLICY (Journal of the Spanish Institute for Strategic Studies, 2018)
In this article we define European Defence (where defence is taken to mean the defence policy of the European Union) using the metaphor of a landscape of changing horizons. Despite the fact that the European defence policy is somewhat unclear and ill-defined, a country like Spain must follow its evolution closely, given that an important part of the country’s future strategic options will be determined by the transformation of either the Common Security and Defence Policy (CSDP) or NATO. If we accept this proposition, we should assess the implications of recent developments in European defence policy for Spanish defence, primarily those stemming from the European Council of December 2013. In this article is offer an answer to this question through an analysis of the nature of European defence policy, recent progress in the area and the opportunities open to Spain